The Effect of the Places of Residence on Health Components in the Quality of Students’ Life - Tsos, Anatolii V.; Цьось, Анатолій Васильович; Andreychuk, Olga; Андрійчук, Ольга; Kasarda, Olga; Касарда, Ольга (Lesya Ukrainka Eastern European National University Lutsk National Technical University (Lutsk), 2014)
The influence of place of residence on the health components in the students’ quality of life was identified in the article. It was established that among the factors that form a physical health component most points belong to the index of physical activity of men (PF = 95,71) and women (PF = 91,43), among the components of the mental health component – index of a social activity of men (SF = 82,9) and women (SF = 77,22) who live in private houses in comparison with residents of flats and dormitories. Life in private houses has a positive influence on the formation of components of life quality compared with the life in dormitories and flats. У статті визначено вплив місця проживання на компоненти здоров’я в якості життя студентів. Установлено, що серед чинників, які формують фізичний компонент здоров’я, найбільше балів визначено за показником фізичної активності чоловіків (PF=95,71) і жінок (PF=91,43), серед складників психічного компонента здоров’я – показник соціальної активності чоловіків (SF=82,9) та жінок (SF=77,22), які проживають у власних будинках, порівняно із мешканцями квартир і гуртожитків. Проживання у власних будинках здійснює позитивний вплив на формування компонентів якості життя, порівняно з мешканцями гуртожитків і квартир.
Вплив місця проживання на компоненти здоров’я в якості життя студентів.
Keywords: health; quality of life; students; place of the residence; здоров’я; якість життя; студенти; місце проживання